2019
DOI: 10.1021/acs.orglett.9b00499
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Catalyzed Remotemeta-C–H Functionalization of Aromatic Tertiary Amines

Abstract: Pd(II)-catalyzed remote C−H olefination of aromatic tertiary amines was achieved with high meta selectivity. With the assistance of an elaborated template, C−H functionalization of unreactive aryl tertiary amines, hindered by the p−π conjugation between the lone-pair electrons of the nitrogen atom and the phenyl ring, was realized with high meta regioselectivity via a quaternary ammonium salt assembly. The results demonstrate that apart from the distance and geometry of the template, the conformation of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…In 2012, Yu and coworkers innovatively developed a U-shaped template that could well overcome the constraint of spatial geometry and accomplished the meta -C–H functionalization of arenes (Figure b) . Subsequently, Yu, Tan, Maiti, Li, Jin, and Kong further established the versatility of this U-shaped template in the meta -C–H functionalization of arenes. In addition, Maiti and coworkers described a palladium-catalyzed remote para -C–H functionalization of arenes with a D-shaped biphenyl template-based assembly (Figure b) .…”
mentioning
confidence: 96%
“…In 2012, Yu and coworkers innovatively developed a U-shaped template that could well overcome the constraint of spatial geometry and accomplished the meta -C–H functionalization of arenes (Figure b) . Subsequently, Yu, Tan, Maiti, Li, Jin, and Kong further established the versatility of this U-shaped template in the meta -C–H functionalization of arenes. In addition, Maiti and coworkers described a palladium-catalyzed remote para -C–H functionalization of arenes with a D-shaped biphenyl template-based assembly (Figure b) .…”
mentioning
confidence: 96%
“…It was shown that selective m -C–H activation was attained by forming a macrocyclic cyclophane-like pretransition state . Subsequently, various research groups, including his group and those of Maiti, Tan, Li, , Jin, and others, have been active in m -C–H functionalization. Recently, our research group also disclosed the new and simple aliphatic nitrile group directing template 2-cyano-2-isobutyl-4-methylpentanoic acid synthesized from simple benchtop starting materials .…”
mentioning
confidence: 99%
“…Accordingly, the development of a reaction system, namely, other than protocols involving electrophilic substitution reactions is highly desirable. Transition-metal-catalyzed direct meta -C–H functionalization reactions of anilines have been recently gathering much attention for this purpose (Scheme c), , realizing various functionalization reactions, such as arylation, borylation, alkylation, chlorination, and olefination, using well-designed ligands and directing groups. However, this state-of-the-art methodology still has some drawbacks, such as overfunctionalization due to equal reactivity between the two meta positions and low efficiency in the reactions of the para -substituted anilines presumably due to the steric repulsion between the neighboring para -substituent and the metal catalyst bound at the meta position in the arylmetal intermediate.…”
mentioning
confidence: 99%